Signs and wonders in Britain's age of revolution
1 online resource.
Keywords: "Signs and Wonders in Britain's Age of Revolution is an original collection of primary sources from the era encompassing the political, religious, and social tumult of the English Civil War. With a focus on Britain in the seventeenth century and covering topics such as astrology, scurrilous pamphlet wars, witch-hunts and trials, and the execution of King Charles I, Signs and Wonders in Britain's Age of Revolution is essential reading for all students of early modern Britain"--